Efficacy of plant extracts for the control of powdery mildew of coriander (Coriandrum sativum L.) - Singh, A K (Journal of Spices and Aromatic Crops, 2008)
Evaluation of five plant extracts namely, Andrographis paniculata, Azadirachta indica, Polyalthialongifolia, Saraca indica and Adina cardifolia for the control of powdery mildew of coriander(Coriandrum sativum), in comparison with wettable sulfur 0.3% indicated that A. paniculataand A. indica were singnificantly superior in reduction of disease severity and incresase ingrain yield over control indicating their potential for use as a component in integreatedmanagement of the disease.